Faktor Moderasi Hubungan Lingkungan Kelembagaan dengan Kompetensi Kewirausahaan Digital Guru di SMK - Aysi, Siti Aenandari Hadatul; Susilaningsih; Muhammad Sabandi (Jurnal Pendidikan Indonesia, 2024)
Entrepreneurship education is a crucial process for digital entrepreneurs in the era of escalating digital transformation. Teachers represent one of the key elements who must possess adequate competencies in teaching digital entrepreneurship. The research aims to analyze the factors influencing the digital entrepreneurship competence of teachers derived from the institutional school environment and the background of business ownership and gender. This research is a quantitative study employing survey methodology, and data collection techniques involving the use of questionnaires. The survey was conducted in 11 Vocational High Schools, comprising 81 teachers. The research findings indicate that institutional environmental support in the form of cognitive, normative, and regulative aspects significantly influences the digital entrepreneurship competence possessed by entrepreneurship teachers. Other influences can be observed from teachers' internal factors (entrepreneurial background and gender), however, these influences have low significance in affecting teachers' digital entrepreneurship competence. Researchers may conduct broader explorations regarding other factors that may influence teachers' digital entrepreneurship competence.